Bahiagrass (Paspalum notatum): Overview and Management - Yoana Newman; Joao Vendramini; Ann Blount (EDIS, 2010)
SS-AGR-332, a 9-page illustrated fact sheet by Yoana Newman, Joao Vendramini, and Ann Blount, provides an overview of this warm-season perennial grass that is widely used in Florida and details of management and production. Includes references. Published by the UF Department of Agronomy, May 2010.